2020
DOI: 10.1177/1043454219897102
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Overweight and Obesity in Childhood Cancer Survivors

Abstract: Purpose: The purpose of this study was to explore the potential risk factors for overweight/obesity in survivors of childhood cancer. Design: A retrospective chart review of childhood cancer survivors ( N = 321) seen in a cancer survivor clinic was conducted to determine the strongest risks of overweight/obesity. Risk factors were as follows: age, race, gender, cancer diagnosis, body mass index at diagnosis, and treatment. Multivariate logistic regression was used to identify risks of overweight/obesity while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…In the GFP, the proportion of children with obesity aged 5 to 12 years increased from 6% in the late 1970s to 13% in 1996 and it has stabilized since the 2000s [44]. Patients with obesity at cancer diagnosis are at high risk of being young adults with obesity, a phenomenon that has been described in the literature [6]. Moreover, we have chosen not to adjust for the lifestyle of the patients and for comorbidities during their lives because we were unable to know whether obesity occurred before or after comorbidities or lifestyle‐related events; the risk is of wrongly attributing a risk factor to the development of obesity when it is, in fact, a consequence of obesity, but also because these comorbidities are also linked to the same risk factors as obesity, which could lead to overadjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the GFP, the proportion of children with obesity aged 5 to 12 years increased from 6% in the late 1970s to 13% in 1996 and it has stabilized since the 2000s [44]. Patients with obesity at cancer diagnosis are at high risk of being young adults with obesity, a phenomenon that has been described in the literature [6]. Moreover, we have chosen not to adjust for the lifestyle of the patients and for comorbidities during their lives because we were unable to know whether obesity occurred before or after comorbidities or lifestyle‐related events; the risk is of wrongly attributing a risk factor to the development of obesity when it is, in fact, a consequence of obesity, but also because these comorbidities are also linked to the same risk factors as obesity, which could lead to overadjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity secondary to hypothalamic-pituitary dysfunction, related to a tumor or surgery in the sellar region, is also a well-known risk factor [7,[9][10][11]. Other parameters have been studied in adult CCSs, independent of the oncological treatment, such as sex, the patient's social environment and status, ethnic origin, body mass index (BMI) at diagnosis, and young age at diagnosis [6,12,13]. Some of these studies presented contradictory results, illustrating the complex influence of the environment on the etiology of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of chronic health condition disparities assessed for non-Hispanic Black survivors included vitamin-D deficiency (27), subsequent neoplasms (31), cardiovascular disorders (31), cardiovascular risks (38), and serious/life-threatening health conditions (43). The type of chronic health condition disparities assessed for Hispanic survivors included vitamin-D deficiency (27), obesity (29), subsequent neoplasm (31), endocrine condition (31) attainment, household income), and lifestyle health risk for chronic health conditions (BMI and cardiovascular risk factors including obesity, diabetes, hypertension and dyslipidemia).…”
Section: Disparities In Chronic Health Conditionsmentioning
confidence: 99%
“…Particularly for Hispanic survivors, family dynamics (e.g., language spoken at home) should be further investigated as they are potentially protective factors for poor patient-reported outcomes. In chronic health conditions, most articles found that racial/ethnic disparities remained statistically significant after risk modulators (e.g., clinical factors, individual demographic and SES factors, and cardiovascular risk factors) were included in the multivariable modeling (27,29,31,38,43). It is possible that underlying biological mechanisms (e.g., inherited genetic predisposition to disease risks and epigenetic modifications due to life experiences or environmental exposures) and disadvantaged neighborhood environments may elevate disparities in chronic health conditions beyond the influence of individual SES and clinical risk.…”
Section: Disparity-specific Risk Modulatorsmentioning
confidence: 99%